2010
DOI: 10.4049/jimmunol.1000314
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of the Activation of the Angiotensin-(1–7) Receptor, Mas, in Experimental Models of Arthritis

Abstract: Activation of the renin-angiotensin (Ang) system induces inflammation via interaction between Ang II and type 1 receptor on leukocytes. The relevance of the new arm of the renin-Ang system, namely Ang-converting enzyme-2/Ang-(1–7)/Mas receptor, for inflammatory responses is not known and was investigated in this study. For this purpose, two experimental models were used: Ag-induced arthritis (AIA) in mice and adjuvant-induced arthritis (AdIA) in rats. Male C57BL/6 wild-type or Mas−/− mice were subjected to AIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
108
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 53 publications
6
108
0
6
Order By: Relevance
“…Further, ANG 1-7 or captopril treatment reduced the expression of several inflammation genes involved in the NF-kB signaling pathway; as a result, it reduced cardiac ischemia-induced dysfunction in diabetic hypertensive rats (Al-Maghrebi et al, 2009). The protective effects of ANG 1-7 were further substantiated by decreased neutrophil accumulation and inflammatory cytokine release in experimental models of arthritis (da Silveira et al, 2010). Interestingly, we could observe increased protein levels of CD68, iNOS, NF-kB and mRNA expressions of IL-1β, IFN-γ and MCP-1 in rats with DCM, and these changes were significantly decreased by telmisartan treatment (Figs.…”
Section: Discussionmentioning
confidence: 81%
“…Further, ANG 1-7 or captopril treatment reduced the expression of several inflammation genes involved in the NF-kB signaling pathway; as a result, it reduced cardiac ischemia-induced dysfunction in diabetic hypertensive rats (Al-Maghrebi et al, 2009). The protective effects of ANG 1-7 were further substantiated by decreased neutrophil accumulation and inflammatory cytokine release in experimental models of arthritis (da Silveira et al, 2010). Interestingly, we could observe increased protein levels of CD68, iNOS, NF-kB and mRNA expressions of IL-1β, IFN-γ and MCP-1 in rats with DCM, and these changes were significantly decreased by telmisartan treatment (Figs.…”
Section: Discussionmentioning
confidence: 81%
“…However, the present results showed that although the effect of Ang-1-7 on blood pressure and paw edema appeared after administration, a greater effect was that exerted on blood pressure and reached a significant level after 10 days, whereas a significant effect on paw edema was obtained after 14 days. This result could be due to the more direct vascular effect of Ang-1-7 by direct inhibition of leukocyte-endothelial cell interaction [21] and downregulation of AT1 receptors on vascular cells [31] , whereas in case of paw edema, a time lag is necessary for downregulating the already upregulated RAS components in the inflammatory cells infiltrating synovium [32] . Moreover, inhibiting cytokines production is consequent to activation of MasR [21] , and since MasR are Gprotein coupled, it is plausible to suggest that the antiinflammatory (decreasing cellular infiltration and edema) effect of Ang-(1-7) is observed after an adequate latency.…”
Section: Discussionmentioning
confidence: 92%
“…The present results showed that Ang-(1-7) reduced TNF-α (but not IL-1β) and paw volume. Accordingly, it is plausible to suggest that the effect of Ang-(1-7) involves reduction of TNF-α displayed systemically, as in this study, and/or within the joint TNF-α [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main peptide of the classical RAS pathway is AngII (angiotensin II) which is associated with a deleterious effect in skeletal muscle [26][27][28][29][30]. The main peptide of the non-classical axis is Ang-(1-7) [angiotensin-(1-7)], which produces its cellular effects through the G-protein-coupled receptor Mas [31][32][33][34]. The Mas receptor is expressed in several tissues, including skeletal muscle [35,36].…”
Section: Introductionmentioning
confidence: 99%